Finite-time boundedness, L2-gain analysis and control of Markovian jump switched neural networks with additive time-varying delays. (February 2017) - Ali, M. Syed; Saravanan, S.; Cao, Jinde
Abstract: This paper is concerned with the problem of finite-time boundedness, L 2 gain analysis and control of Markovian jump switched neural networks (MJSNNs) with additive time-varying delays. Sufficient conditions to guarantee finite-time bounded of MJSNNs with additive time-varying delays are presented. These conditions are delay-dependent and are given in terms of linear matrix inequalities (LMIs). Moreover, finite-time L 2 -gain analysis of switched neural networks with additive time-varying delays are given to measure its disturbance tolerance capability in the fixed time interval. In addition finite-time control of MJSNNs is studied. Detailed proofs are accomplished by using Lyapunov-functionals and average dwell time approach (ADT). Finally, numerical example is given to demonstrate the effectiveness of the proposed approach.